Power quality and custom power improvement using UPQC - Swapna Sai, P; G. Rajasekhar, G; Vijay Muni, T; Sai Chand, M (International Journal of Engineering and Technology, 2018)
The Series and Shunt units donâ€™t have a typical dc link. So their control systems not exactly as same as the traditional UPQC control strategies.This device can improve power quality and composes power electronic series which was in MV/LV Substation, alongside a few electronic-shunt units associated near the end users.Additionally, the increment in power quality can be given to the users we require the shunt units.It reduces the disturbances for all customers that supply main series unit. It provides the customerwith the shunt units. A proposed solution model of LV grid is 400-KVA is considered as steady-state performance and functionalizing units. Outcomes acquired under enduring state conditions justify the design picked and great gadget execution.Â Â